Reducing the Impact of Seasonality on the Tourist Guide Profession by Studying the Model of the Jeddah Tour Guides Cooperative in the City of Jeddah - Dr. Afnan Abdulrahman Bahanshal (Journal of Arts, Literature, Humanities and Social Sciences, 2026)
Although the tourist guide profession is considered a pillar of a successful tourist industry, due to its effective role in introducing tourists to a destination’s history, culture, local people, and community, it faces many challenges and difficulties. The seasonality of tourism activity is one of the most prominent of those challenges. This research aims to study this question by focusing on the Jeddah Tour Guides Cooperative in the city of Jeddah, one of whose objectives is reducing the impact of seasonality. To achieve the research aims and objectives, interviews were conducted with 20 licensed tourist guides and members of the Jeddah Tour Guides Cooperative, using semi-structured interviews. The research provides an overview of the association, defining its vision, mission, and goals as well as the services it offers to tourists and its tour guide members. The results show that, due to seasonality, tourist guides suffer from financial and employment problems on which the strategies, plans, and solutions implemented by the Jeddah Tour Guides Cooperative are having an impact. Several solutions to address financial problems are suggested, including diversifying tourism, establishing agreements with parties relevant to the tourism sector, improving member qualification and training, promoting the cooperative’s activities and ensuring investment in both members and tourism. Employment problems can be tackled by reducing tourist guide fees, utilizing tourist guides at events and festivals and obtaining employment recommendations. The study calls for such cooperatives to be established locally in different cities and provinces in the Kingdom of Saudi Arabia as well as internationally.